TEOLOGI PEMBEBASAN DALAM TEKS WRSPATI TATTWA - Putu Sri Marselinawati (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The Wrspati Tattwa text is the core teachings of the Sang Hyang Isvara and Rsi Wrspati dialogue. Wrspati Tattwa texts are Sanskrit and Old Javanese The Wrspati Tattwa text is the result of an adaptation of the Sankhya teachings and Yoga Sutra and some of the concepts of the Shiva siddhanta teachings that originally developed in South India. In this article, 5 basic concepts of Hindu liberation theology are derived from the concept of Panca Sradha, the concept of God or Widhi Tattwa mentions in the Wrspati Tattwa text God as the creator is dwaita 'dualistic' which means there are two principles that cause everything. Namely Cetana and Acetana. Cetana is a conscious principle called Shiva Tattwa, which consists of Tri Purusha. Atma Tattwadalam Wrspati Tattwa text comes from Siwatma. The element of thought contained in creation influences karma and reincarnation. Prayogasandi's path on how to connect with God through sense knowledge and control,yoga as a way of liberation to achieve happiness and authenticity. Sad angga Yoga is one of the paths of Yoga that was delivered by Sang Hyng Isvara to Rsi Wrspati as a way to achieve liberation. The parts of sad angga yoga are pratyahara, dhyana, pranayama, dharana, tarka, and samadhi.